Simulation Of Irrigation Area by Using Dependable Flow Basic Year And Basic Month - Juppy Damay Lantika; A Zakaria; D. I. Kusumastuti (Journal of Engineering and Scientific Research, 2021)
The purpose of this study was to analyze the availability of irrigation water from the reservoir by using a dependable flow of basic month, analyze the availability of irrigation water from the reservoir by using the dependable flow of basic year and compare the calculation of the availability of irrigation water from the reservoir by using a dependable flow of basic month and the basic year, Where which is more effective.    The research was conducted using secondary data, the research location was in Way Rarem Reservoir, data obtained from the Mesuji-Sekampung River Basin Center and the North Lampung Geophysics Station UPT. Analysis of the data calculates the availability of irrigation water and irrigation water needs, to determine the maximum irrigation area that can be irrigated. The availability of irrigation water is made of two types of calculations, first using the basic month dependable flow with a reliability of 40%, 50%, and 60%, and the second with the basic year dependable flow from 2011-2020. Irrigation water needs are calculated using a modified penman, with a cropping pattern used of Paddy-Paddy-secondary crop and 4 groups. The results of this study are the basic year dependable flow gets an irrigation area of ??1328,65 Ha and the basic month dependable flow gets an area of ??11186,83 Ha, the basic dependable flow area gets a larger area than the basic month dependable flow, the maximum area of ??dependable flow basic month and basic year in Group IV started on January 1.